Análisis de la ejecución presupuestal y el cumplimiento de las metas en la Municipalidad Provincial de Maynas en el periodo 2020 - 2021 - Ramirez Celis, Selma Luz (2023)
The research is entitled "Analysis of Budget Execution and Goal Fulfillment in the Provincial Municipality of Maynas 2020-2021" and its general objective is to determine the incidence of budget execution in the fulfillment of goals in the Provincial Municipality of Maynas in the period 2020 – 2022 Our variables: budget execution (dependent variable) and achievement of goals (independent variable) have a study period of 2020-2021. Through a theoretical framework, we solidify the importance of budget execution and its behavior against the achievement of goals. After the processing and analysis of the data collected, we obtained results that show an upward trend in their behavior in the case of budget execution and an increase in their behavior in the case of meeting goals, that is, each year both have a proportional increase., which means that it is positively correlated. In conclusion, through the analysis it can be verified that the budget execution affects the municipality of Maynas to achieve the goal in the period 2020-2021.